Pharmacophore-based approach for the identification of prospective UDP-2,3-diacylglucosamine hydrolase (LpxH) inhibitor from natural product database against Salmonella Typhi - Divyapriya Karthikeyan; Sanjit Kumar; NS Jayaprakash (Chemical Physics Impact)
Antibiotics are essential for the treatment of typhoid fever, which is caused by Salmonella Typhi. The global increase of antibiotic resistance in S. Typhi is a significant public health threat. The traditional approach to discovering new drugs is a lengthy process. To address this, ligand-based pharmacophore modeling was used to identify potential inhibitors of the S. typhi LpxH protein, a crucial enzyme in the lipid A biosynthesis pathway. A natural compound library of 852,445 molecules was screened against a pharmacophore model developed from known LpxH inhibitors. Further, virtual screening, molecular docking, and MD simulation (100 ns) studies identified two lead compounds, 1615 and 1553. A comparative analysis of both molecules showed that compound 1615 exhibited the highest stability, with the lowest potential energy, minimal fluctuations, and stable hydrogen bonding, indicating strong binding at the active site. Compound 1553 also demonstrated good stability, though with slightly higher fluctuations. Both compounds underwent toxicity prediction and ADMET analysis, showing favorable drug-like properties, with compound 1615 emerging as the most promising inhibitor due to its optimal electronic energy and minimal chemical potential. The study concluded that compounds 1615 and 1553 hold significant potential as lead molecules for developing new treatments against drug-resistant S. Typhi infections. This study illustrates how computational techniques, such as MD simulations and pharmacophore modeling, can speed up drug discovery, especially in the fight against antibiotic resistance.